2015
DOI: 10.1108/ejtd-01-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Canadian chefs’ workplace learning

Abstract: Purpose – This paper aims to examine the formal and informal workplace learning of professional chefs. In particular, it considers chefs’ learning strategies and outcomes as well as the barriers to and facilitators of their workplace learning. Design/methodology/approach – The methodology is based on in-depth, face-to-face, semi-structured interviews with 12 executive chefs from a variety of restaurant types. Chefs were asked questions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Finally, continuous learning is mandatory for chefs' success because it increases their efficiency and their professional knowledge and skills (Cormier et al, 2015).…”
Section: Acquiring Needed Skills and Competencementioning
confidence: 99%
See 4 more Smart Citations
“…Finally, continuous learning is mandatory for chefs' success because it increases their efficiency and their professional knowledge and skills (Cormier et al, 2015).…”
Section: Acquiring Needed Skills and Competencementioning
confidence: 99%
“…When it comes to facilitators, they reported that "internal and external networks" become particularly a key factor for chefs (Cormier-MacBurnie et al, 2015). Women, in parti-cular, when they start their career in the kitchen, need to integrate into the workplace and to demonstrate their strength and ability to equal their male colleagues who may not lose the opportunity to test them and to verify that they can bear the job like they do (Black, 2015;Harris and Giuffre, 2015, p. 85).…”
Section: Workplace Learning: Needed Skills Barriers and Facilitatorsmentioning
confidence: 99%
See 3 more Smart Citations